Hubungan Antara Asupan Protein, Zat Besi (Fe) Dan Vitamin CDengan Kejadian Anemia Pada Siswi Smk PenerbanganBina Dhirgantara Karanganyar - Denistikasari, Rossita; , Dwi Sarbini, SST, M.Kes; , Ahmad Farudin, SKM, M.Si (2016)
Background : The increase of nutrient intake particularly for girls during growth is very important. Optimum health level, requires balance nutrient intake. One of nutritional problems happens mostly among girls is anemia. Anemia is the impact low intake of macro-nutrients, i.e. carbohydrates, proteins, fats and micro-nutrients, i.e. vitamins and minerals. The impacts of anemia are stunted growth, weak physical body, and low enthusiasm for learning / achievement. Objective : To determine correlations between intakes of protein, iron (Fe) and vitamin C and anemia in girls at Bina Dhirgantara Flight Vocational High School of Karanganyar. Methods : This study was an observational analytic with cross sectional design. Subjects were 38 students of class XI and XII Bina Dhirgantara Flight Vocational High School of Karanganyar. Data collection of subject identity used of questionnaire. Data on intakes of protein, iron (Fe) and vitamin C were obtained used a 24-hour food recall and hemoglobin levels used hemoglobin Cyanmeth method. Analysis of data used Kolmogorof Smirnov test for normality test and Pearson Product Moment test for statistical analyzis. Results : Students who were anemia was 71.1%, who had low protein intake was 63.2%, who had low intake of iron (Fe) was 68.4%, and who had low intake of Vitamin C was 86.8%. Analytic test result obtained there was a significant correlation between anemia and protein intake and the intake of iron (Fe). There was no significant correlation between vitamin C intake and anemia at Bina Dhirgantara Flight Vocational High School of Karanganyar. Conclusion : There was a significant correlation between anemia and protein intake (p = 0.015) and the intake of iron (Fe) (p = 0.017). There was no significant correlation between vitamin C intake and anemia (p = 0.920) at Bina Dhirgantara Flight Vocational High School of Karanganyar.